Pengaruh Fomo Terhadap Impulse Buying Saat Live Streaming pada Pengguna Shopee di Kota Medan - Hasman, Haryaji Catur Putera; Irza, Novia Aishwarya; Yunita, Nindya; Alfifto, Alfifto (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to determine the Effect of FOMO and Sales Promotion on Impulse Buying during live streaming on Shopee users in Medan. The population in this study is Consumers have made product purchases on Shopee live streaming So the respondents who will be sampled in this study are 110 Shopee users who live in Medan City. Results of the FOMO hypothesis test on Impulse Buying The test results of FOMO on Impulse Buying have a P-Values of 0.000 and t-Statistics 4.598 or this value has P-Values, 0.05 and t-statistics >1.96. this means that FOMO has a significant effect on Impulse buying. Sales Promotion to Impulse Buying The results of testing the hypothesis of Sales Promotion to Impulse Buying have a P-Values value of 0.000 and t-Statistics 5.915 or this value has P-Values 0.05 and t-statistics 1.96. This means that Sales Promotion has a significant effect on impulse buying.